Study of the germination and morphology of the post-seminal development of Syngonanthus mucugensis Giul. “in vitro” - Silva, José Roberto S.; Santos, Janilza da Paixão; Rios, Ana Paula S.; Santana, José Raniere F.; Dornelles, Ana Lúcia C. (SITIENTIBUS série Ciências Biológicas, 2005)
Syngonanthus mucugensis (Eriocaulaceae) grows in the “rupestres” fields of Bahia. Its economic importance rests in the use of both the stem and flowers in crafts, making extractivism an important economic activity within its distribution. Indiscriminate collecting is threatening populations of the species. This study sought to evaluate germination and post-seminal development of S. mucugensis in vitro, seeking to supply information for future works. After asepsis and water uptake for 24 hours, the seeds were placed to germinate in petri dishes under controlled conditions of light and darkness. In each petri dish, 20 seeds were placed on a culture mediun for germination (agar 7 g.L-1), with pH 5.7 adjusted prior to autoclaving (1 atm, 121ºC and 15 min). The results showed that the seeds of S. mucugensis need light to germinate, the germination is of the hypogeal type with success rate of 85%. The first phase of the post-seminal development begins with the protrusion of the embryonic axis from which the leaves and the radicular system are simultaneously developed. Approximately 25 days after the germination, the plants presented average length of 10 mm, about four leaves with malphigiaceous tricomes distributed along the margins and a radicular system consisting of two roots.